IMPLEMENTASI PROGRAM PEMBERDAYAAN ANAK JALANAN PADA DINAS SOSIAL KOTA PROBOLINGGO (Studi Kasus Gelandangan, Pengemis dan Pengamen Kota Probolinggo) - Husni Mubarog; Diska Cintya Veredila (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The purpose of this research is to find out and describe the implementation of the Street Children Empowerment Program at the Probolinggo City Social Service and to find out what programs are related to street children empowerment carried out by the Probolinggo City Social Service. This research method uses a qualitative approach with a qualitative descriptive research type, this research method uses interviews and the sample is determined using observation and documentary techniques, data analysis of information collection, data reduction, data presentation at the final stage of drawing conclusions. The Probolinggo City Social Service has a strategy for dealing with street children such as providing guida to street children, increasing guidance to families of street children, skills for street children, namely through screen printing, sewing and computer training programs with this program being very beneficial for street children and street children have creativity. There is also a basic food assistance program for street children, namely assistance with sugar, cooking oil or other basic food assistance with this basic food assistance for the concern of the Probolinggo City Social Service for street children. This strategy was implemented in an effort to provide provisions for street children so that they can interact and have better ethics in society in accordance with decency. Keywords : Program Implementation, Empowerment, Streer Children.